The Emergence and Maintenance of Vector-Borne Diseases in the Khyber Pakhtunkhwa Province, and the Federally Administered Tribal Areas of Pakistan - Nieto, Nathan C.; Khan, Khalid; Uhllah, Ghufran; Teglas, Mike B. (Frontiers in Physiology, 2012)
Human populations throughout much of the world are experiencing unprecedented changes in their relationship to the environment and their interactions with the animals with which so many humans are intimately dependent upon. These changes result not only from human induced changes in the climate, but also from population demographic changes due to wars, social unrest, behavioral changes resulting from cultural mixing, and large changes in land-use practices. Each of these social shifts can affect the maintenance and emergence of arthropod vectors disease or the pathogenic organisms themselves. A good example is the country of Pakistan, with a large rural population and developing urban economy, it also maintains a wide diversity of entomological disease vectors, including biting flies, mosquitoes, and ticks. Pathogens endemic to the region include the agents of piroplasmosis, rickettsiosis, spirochetosis, and viral hemorrhagic fevers and encephalitis. The northwestern region of the country, including the Khyber Pakhtunkhwa Province (KPK), formerly the North-West Frontier Provence (NWFP), and the Federally Administered Tribal Areas (FATA) are mountainous regions with a high degree of habitat diversity that has recently undergone a massive increase in human population density due to an immigrating refugee population from neighboring war-torn Afghanistan. Vector-borne diseases in people and livestock are common in KPK and FATA regions due to the limited use of vector control measures and access to livestock vaccines. The vast majority of people in this region live in abject poverty with >70% of the population living directly from production gained in animal husbandry. In many instances whole families live directly alongside their animal counterparts. In addition, there is little to no awareness of the threat posed by ticks and transmission of either zoonotic or veterinary pathogens. Recent emergence of Crimean–Congo hemorrhagic fever virus in rural populations, outbreaks of Dengue hemorrhagic fever have been reported in the region, and high prevalence of cattle infected and co-infected with multiple species of hemoparasites (Theileria, Babesia, Anaplasma). The emergence of which has followed the increased density of the rural population due to an influx of refugees from violent conflicts in Afghanistan and is exacerbated by an already impoverished society and wide diversity of potential arthropod vectors. These human outbreaks may be exacerbated by episodes of social upheaval but are also tied to the historically close association of people in the region with their livestock and subsequent zoonosis that result from spillover from co-habitation with infected domestic animals.